Socio-Environmental Risk Profiles Associated with Rural Activities in the Localities of the Pool Department, Republic of the Congo - Makaya, Helischa Audrey; Ifo, Suspense Averti (European Scientific Journal, ESJ, 2026)
Local environmental planning requires diagnostic tools capable of identifying areas and activities that may place pressure on soils, fragile environments and water resources before these pressures become measurable deforestation or forest degradation. This study characterises socio-environmental risk profiles associated with rural activities in seven localities of the Pool Department, Republic of the Congo, using an environmental and social field database. Unlike studies centred on community perceptions or satellite time series, the analysis is deliberately restricted to environmental observations: activity types, localities, proximity to rivers or water points, reported risks to fragile environments, risks to rivers and lakes, soil instability and potential conflicts. Variables relating to sub-projects and direct beneficiaries were not used. The results show that agriculture dominates most localities, whilst Mindouli displays a mixed agro-pastoral profile, Koubola a distinctive pastoral profile, and Yalavounga, Yangui and Linzolo very high hydrological sensitivity. Reported risks to fragile environments and water resources are particularly visible in Missafou, Yalavounga and Linzolo. The paper proposes an environmental vigilance typology distinguishing multi-activity, agricultural-riparian, mixed agro-pastoral and pastoral profiles. This typology offers a practical basis for prioritising local environmental monitoring, riparian protection and the introduction of agroecological practices in rural landscapes of the Pool Department.